Tectonically controlled drainage evolution in Lokris (Central Greece) - ΜΑΡΙΟΛΑΚΟΣ, Η.; ΚΡΑΝΗΣ, Χ.; ΜΑΡΟΥΚΙΑΝ, Χ.; ΦΟΥΝΤΟΥΛΗΣ, Ι. (Bulletin of the Geological Society of Greece, 2001)
This paper presents the results of our research in the area of Lokris (Central Greece), regarding the relationship between the neotectonic structures and the response of the drainage network, which is found to be tectonically controlled to a great degree. Neotectonic mapping, geometrical and kinematic analysis, and morphotectonic investigation have shown that the local neotectonic grain is attributable to torsional deformation.